How Can Doxorubicin Loading Orchestrate in Vitro Degradation Behaviors of Mesoporous Silica Nanoparticles under a Physiological Condition? - Choi, Eunshil; Kim, Sehoon (AMER CHEMICAL SOC, 2017)
In the field of drug-delivery research, mesoporous silica nanoparticles (MSNs) have received a great deal of attention because of their capability to load and release drug molecules through the internal mesopores. To maximize the biomedical applicability of MSN-based drug carriers, it is important to ensure their degradability in a physiological environment as well as to obtain MSNs with desirable physicochemical properties. We present in vitro degradability of drug-loaded MSNs (DMSNs) that contain an anticancer drug (doxorubicin) in the pores and are suspended in physiological media (i.e., PBS at 37 degrees C). To obtain comprehensive understanding of the degradation process of DMSNs, cargo free MSNs and nonporous solid silica nanoparticles (SSNs) were studied comparatively. Degradation of each particle was studied by using ICP, TEM, and gas sorption measurement and analyzed in terms of structural parameters, external particle surface dissolution, and acidity of the PBS. It is demonstrated for the first time that drug loading into the pores leads to better degradability of MSNs by combining each distinct advantage of bare MSNs and SSNs to make DMSNs simultaneously possess an initial degradation rate as fast as drug-unloaded MSNs and a total degradation quantity as high as SSNs. The presented data not only demonstrate a high biodegradability of MSN-based drug carriers but also provide new insights into their unique in vitro degradation pattern.
Keywords: SIMULATED BODY-FLUID; DRUG-DELIVERY; CONTROLLED-RELEASE; SIZE; SURFACE; SYSTEM; MCM-41; NANOMEDICINE; KINETICS; SPHERES